Cooperative Stad Type Using Microsoft Power Point in Learning To Improve Motivation And Achievement Learning Mathematics - Suartawan, I Gusti Made (Jayapangus Press, 2024)
A study aimed (1) the students to have motivation (2) in students' mathematics learning achievement had increased. The implementation was carried out in several cycles and the subjects were class XII MIPA 4 students at SMA Negeri 1 Susut year 2021/2022. There were 18 male students and 16 female students from 34 students in this class. These data were: the use of a questionnaire on students' learning motivation in learning mathematics to find out motivational data and learning achievement was searched using tests. The results showed that: (1) students had learning motivation (average score of 69.71 belonging to the sufficient category in activity I increased to 79.35 in the high category in activity II); (2) there was an increase in student learning achievement (the average value of 69.41 in activity I increased to 76.68 in activity II). Overall learning achievement increased from 88% in activity I to 100% in activity II. Based on the results of the research, the Cooperative Model with Microsoft Power Point has increased learning motivation and learning achievement in mathematics in class XII MIPA 4 SMA Negeri 1 Susut on Even Semester year 2021/2022. For this reason, this learning model deserves to be considered as a learning model in the classroom.